Using A Water Quality Index to Assess The Impacts of Heavy Metals Contamination for Sustainable Water Management: A Case Study of the Bang Pakong River, Thailand - Khin Yadana Soe; Pokchat Chutivisut; Wilailuk Niyommaneerat (Applied Environmental Research)
Anthropogenic activities such as improper waste disposal, excessive fertilizer use, and industrial effluents cause heavy metal contamination in water, soil, and the atmosphere. Herein, the water quality index (WQI) was used to characterize heavy metal (i.e., cadmium (Cd), arsenic (As), and mercury (Hg)) contamination in the Bang Pakong River, Thailand. Specifically, water samples were collected during the dry season from four stations along the river from 2012–2022. The heavy metal concentrations in the samples were analyzed via atomic absorption spectrophotometry, and WQI values were calculated on the basis of standard water quality parameters. At the four sampling stations, high As concentrations were observed, and the Cd and Hg concentrations were below the detection limits. The WQI values in the 10-year period indicated good water quality on average. However, the WQI values decreased from 2020–2021, followed by a recovery to medium levels in 2022. The WQI reflects heavy metal contamination of local communities in an easy-to-understand manner, revealing its effect on aquatic environments and their health and livelihood.